(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article discusses the life and work of Mambetimin uulu Kazybek, famous in the Kyrgyz people by his works. It is noted that artificial obstacles were created in the way of Kazalchi (works of the writing poets) creativity, and persecution was arranged by falsifying the accusations. The question of dissemination and closer acquaintance with Kazybek Mambetimin uulu creativity is raised.